Design considerations of III-nitride-based two-dimensional photonic crystal cavities with crystallographically induced disorder. (11th November 2021) - Iwaya, Takenori; Ichikawa, Shuhei; Murakami, Masato; Timmerman, Dolf; Tatebayashi, Jun; Fujiwara, Yasufumi
Abstract: We present a study on the improvement of quality factors ( Q -factors) of III-nitride-based two-dimensional photonic crystal (2D-PhC) nanocavities. Although III-nitride-based 2D-PhC cavities have been studied for long time, they typically show relatively low experimental Q -factors due to disorders inevitably introduced during the fabrication processes. In order to realize high- Q -factors, it is necessary to introduce cavities that are tolerant to disorder. We numerically reproduce the experimental found disorder in simulations, and discuss the influence of disorder on Q -factors of several types of cavities. We demonstrate the suitability of these cavities for the realization of high- Q -factors, and show which structures have the largest tolerance for disorders.